STRUCTURAL CHARACTERIZATION OF NPAS4-ARNT DIMERIZATION THROUGH COMPUTATIONAL SIMULATION (Proceedings of International Conference on BioScience and Biotechnology, 2019)
Neuronal PAS Domain Protein 4 (Npas4) is an activity dependent transcription factor harboring basic helix-loop-helix (bHLH)-PAS domain, mediating the expression of target genes involved in neuro-transmission. NPAS4 crucially regulates response to various excitatory stimuli and has a role in GABAergic neuronal synapse development. Functionally, NPAS4 as a transcription factor dimerizes with the ARNT protein to serve as complete transcription factor and start the transcription of downstream genes. However, NPAS4 dimerization characteristics with ARNT has not been studied so far. Hence the current study aimed to identify the interaction pattern of NPAS4-ARNT complex through computational docking via HADDOCK. The interaction pattern were determined through pdbSum. The electrostatic surface calculations were performed through APBS plugins in PyMOL. The results indicated that PASB domain of NPAS4 is involved in interactions with the PAS B domain of ARNT. A toll of 136 structures generated by HADDOCK were further grouped into 14 clusters. The cluster with the minimum energy value of -82.6 KJ/mol was then further selected for interaction analysis. The results showed that there is one salt bridge, 12 H-bonding interactions and 156 non-bonded contacts between two proteins. The important interactions among two proteins are Asp224:NPAS4 and Gln421:ARNT, Asp229:NPAS4 and Ser442:ARNT, Glu232:NPAS4 and Thr361:ARNT, Phe240, Glu241:NPAS4, and Arg440:ARNT. The electrostatic potential of these two proteins revealed the binding interface of NPAS4 and ARNT to be neutral hence favoring hydrophobic interactions.  The findings can help elucidate Npas4 role in interacting with other neuronal proteins involved in neuronal signaling. Moreover, the interaction findings provide useful comparative insight with other bHLH proteins.
Keywords: NPAS4; bHLH proteins; dimerization; neurotransmission; molecular simulation